PENGARUH SOCIAL MEDIA MARKETING, E-COMMERCE, DAN KUALITAS PRODUK TERHADAP PENINGKATAN PENJUALAN TOKO OFFLINE PADA FAMILY BUSINESS UNIVERSITAS CIPUTRA ANGKATAN 9 - Gunarto, Williams Sentoso; Susanto Pranoto, Henry (PERFORMA, 2023)
The purpose of this research is to find out the effect of Social Media Marketing, E-commerce, and Product Quality on increasing offline store sale of ninth batch Universitas Ciputra family business. This research uses quantitative approach with the number of 119 population , the samples that is taken as many as 92 with Slovin formula. Sampling uses non-probability sampling technique with the criteria of having offline business and using social media and e-commerce. This research is processed using SPSS software, data collection method uses questionnaire that is distributed online through google form. The result of this research indicates that Social Media Marketing does not affect significant on increasing sale, e-commerce can increase sale significantly, and Product Quality does not affect significant on increasing sale.